Social psychology of social problems : the intergroup context - Golec, Agnieszka; Cichocka, Aleksandra (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2013)
"Encompassing contemporary social problems and cutting-edge research, top international experts provide a window into understanding the psychology behind societal problems and why they develop, offering crucial applications of psychological theory for the undergraduate student."--Publisher's website.
Part 1: Racism, sexism and social discrimination. Negative stereotypes, prejudice and discrimination / J. Christopher Cohrs and Thomas Kessler ; The social context of racism / Christopher M. Federico ; Antecedents and manifestations of sexism / Janina Pietrzak ; Towards an understanding of immigration as a defining feature of the twenty-first century / Leah K. Hamilton, Stelian Medianu and Victoria M. Esses. -- Part 2: Inequality, tyranny, violent and non-violent social protest. The corrupting power of social inequality: social-psychological consequences, causes and solutions / Robbie M. Sutton, Aleksandra Cichocka and Jojanneke van der Toorn ; Social conflict and social protest / Jacquelien van Stekelenburg and Bert Klandermans ; Obedience and Tyranny in Psychology and history / Stephen D. Reicher and S. Alexander Haslam. -- Part 3: Intergroup violence, extremism and terrorism. Extreme forms of ingroup positivity and their negative consequences for intergroup relations / Agnieszka Golec de Zavala and Rober T. Schatz ; The role of threats in understanding and improving intergroup relations / Walter G. Stephan ; Why society members tend to support the continuation of intractable conflicts and resist peaceful resolution / Daniel Bar-Tal, Eran Halperin, Roni Porat and Rafi Nets-Zehngut ; Evil transformations: Social-psychological processes underlying genocide and mass killing ; Michal Bilewicz and Johanna Ray Vollhardt ; The social psychology of terrorism: individual, group and organizational processes / Keren Sharvit and Arie W. Kruglanski. -- Part 4: Towards applying social psychology. Applying social psychology to understanding social problems / Robert A. C. Ruiter, Karlijn Massar, Mark van Vugt and Gerjo Kok.
Includes bibliographical references and index.
Keywords: Social problems -- Psychological aspects; Social psychology; socijalni problemi; socijalna psihologija